2011
DOI: 10.1186/1546-0096-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of fibrinogen as a target of citrullination in IgM rheumatoid factor-positive polyarticular juvenile idiopathic arthritis

Abstract: BackgroundSeveral studies have noted the significance of measuring anti-cyclic citrullinated peptide (CCP) antibodies in juvenile idiopathic arthritis (JIA) as an important indicator for destructive disease, as is the case in rheumatoid arthritis (RA). While the role of anti-CCP antibodies in RA and JIA has become better understood, the identity of the target proteins of this modification has remained elusive. In this study, we evaluated serum from patients with various subtypes of JIA to investigate the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Our findings showed that the prevalence rates of all ACPAs in the whole population of JIA patients were less than 30% and much lower than those of adult RA patients, which agrees with the results reported in previous studies on anti-CCP (Avcin et al, 2002;Bongi et al, 2004;Kasapçopur et al, 2004;Kwok et al, 2005;Gilliam et al, 2011;Tebo et al, 2012). Therefore, we confirmed that ACPAs cannot serve as screening biomarkers for the general JIA population due to their low sensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings showed that the prevalence rates of all ACPAs in the whole population of JIA patients were less than 30% and much lower than those of adult RA patients, which agrees with the results reported in previous studies on anti-CCP (Avcin et al, 2002;Bongi et al, 2004;Kasapçopur et al, 2004;Kwok et al, 2005;Gilliam et al, 2011;Tebo et al, 2012). Therefore, we confirmed that ACPAs cannot serve as screening biomarkers for the general JIA population due to their low sensitivity.…”
Section: Discussionsupporting
confidence: 81%
“…Fibrinogen plays roles in blood clotting, fibrinolysis, cellular and matrix interactions, the inflammatory response, wound healing and neoplasia [33]. Recent findings have shown that fibrin plays key roles in both inflammatory response and the development of RA [34], and fibrinogen levels correlate closely with ESR in RA patients [35]. Indeed, ESR might be influenced by several factors other than inflammatory response, such as anemia and aging.…”
Section: Discussionmentioning
confidence: 98%
“…The fibrinogen molecule is a soluble, large plasma glycoprotein that is converted by thrombin into fibrin during blood clot formation [3]. Fibrinogen is synthesized in the liver by the hepatocytes [9]. Research from 2011 has shown that fibrin plays a key role in the inflammatory response and development of rheumatoid arthritis [10].…”
Section: Introductionmentioning
confidence: 99%